Influence of Excitation Signal on Impedance-based Structural Health Monitoring - Baptista, Fabricio Guimaraes; Vieira Filho, Jozué [UNESP]; Inman, Daniel J. (Sage Publications Ltd, 2010)
The electromechanical impedance (EMI) technique has been successfully used in structural health monitoring (SHM) systems on a wide variety of structures. The basic concept of this technique is to monitor the structural integrity by exciting and sensing a piezoelectric transducer, usually a lead zirconate titanate (PZT) wafer bonded to the structure to be monitored and excited in a suitable frequency range. Owing to the piezoelectric effect, there is a relationship between the mechanical impedance of the host structure, which is directly related to its integrity, and the electrical impedance of the PZT transducer, which is obtained through the ratio between the excitation and sensing signals. This work investigates the influence of the type of excitation signal and voltage level on impedance-based monitoring systems. To illustrate our conjecture, tests have been carried out on an aluminum specimen with different health conditions and the results show conclusively that the excitation signal has influence on system performance and power dissipation in the PZT transducer.
Keywords: structural health monitoring; impedance; piezoelectric transducer; excitation signal